Entre desenhos, cores e histórias: proposta de material didático para o museu de Vacaria/RS - Rodrigues, Manoela Grazziotin (My University, 2022)
This research studies the Local History of the town of Vacaria, from the collection of the Town Museum Dr. Adhemar Antonio Martins Pinotti, located northeast of the state of Rio Grande do Sul. It presents a historical narrative of the constitution of the town, deepening the economic and political analysis of the 1970s and 1980s, the period that preceded the construction of Casa do Povo - Centro Cultural Marcos Palombini, the only building designed by the architect Oscar Niemeyer in Rio Grande do Sul. Since 2020, Casa do Povo has housed the Municipal Library Theobaldo Paim Borges and the Town Museum Dr. Adhemar Antonio Martins Pinotti, memoirist who conducts research on the History of Vacaria and the region. This work aims to contribute to the teaching of History in the basic education stage, Early Childhood Education. It offers a proposal of didactic material for children aged between 4 and 5 years old. It is a textbook/e-book for the Town Museum of Vacaria which, through its collection, will transmit selections from the history of the municipality in a playful way. The interdisciplinary proposal brings drawings for coloring and creation, games and reflective questions The content is specially planned and developed for the young audience. It is pointed out that this material can also be adapted by education professionals, in order to be used in other stages of basic education. In this concern of teaching History since childhood, some theoretical references that contribute to the study are analyzed, approaching concepts of Local History, Museum operation, production of historical awareness in childhood and the use of teaching materials in memory spaces. The dissertation is aligned with the area of concentration in History Teaching of the Postgraduate Program in History at the University of Caxias do Sul. [resumo fornecido pelo autor]
Esta pesquisa estuda a História Local do município de Vacaria, a partir do acervo do Museu Municipal Dr. Adhemar Antonio Martins Pinotti, localizado a nordeste do estado do Rio Grande do Sul. Apresenta uma narrativa histórica da constituição do município, aprofundando a análise econômica e política das décadas de 1970 e 1980, período que antecedeu a construção da Casa do Povo - Centro Cultural Marcos Palombini, única edificação projetada pelo arquiteto Oscar Niemeyer no Rio Grande do Sul. Desde o ano de 2020, a Casa do Povo abriga a Biblioteca Municipal Theobaldo Paim Borges e o Museu Municipal Dr. Adhemar Antonio Martins Pinotti, memorialista que realiza pesquisas sobre a História de Vacaria e região. Esse trabalho visa contribuir para o ensino de História na etapa do ensino básico, Educação Infantil. Oferece uma proposta de material didático para crianças que apresentem faixa etária de 4 a 5 anos. Trata-se de um livro/e-book didático para o Museu Municipal de Vacaria que, através do seu acervo, transmitirá de forma lúdica seleções da história do município. A proposta interdisciplinar traz desenhos para colorir e criar, jogos e questões reflexivas. O conteúdo é especialmente planejado e desenvolvido para o público mirim. Aponta-se que esse material também pode ser adaptado pelos profissionais de educação, a fim de ser utilizado em outras etapas do ensino básico. Nesta preocupação do ensino de História desde a infância, são analisados alguns referenciais teóricos que contribuem para o estudo, abordam conceitos de História Local, operacionalidade do Museu, produção de consciência histórica na infância e uso de materiais didáticos em espaços de memória. A dissertação está alinhada a área de concentração em Ensino de História do Programa de Pós-Graduação em História da Universidade de Caxias do Sul. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Museus - Vacaria (RS); Material didático; Educação de crianças; History - Study and teaching; Museums - Vacaria (Brazil); Courseware; Education of children